Science, Technology, and Opportunity: An Unmanned Aerial Vehicle (UAV) Seminar - Prasetyo, Ilham; Alfakihuddin, Muhammad Lukman Baihaqi; Lestari, Tika Endah; Setiawan, Iwan; Maindratama, Abdullah (Journal of Community Services: Sustainability and Empowerment, 2024)
UAVs, known as drones, are operated with no onboard pilot. In the last decade, there has been a rapidly growing improvement in the drones pertinency in multiple areas. The use of UAVs has increased in the science, technology, engineering, and mathematics (STEM) professions. There is a growing need to integrate UAV training into STEM education. Several studies have been conducted on UAVs, and some opportunities could be gained from this area. These opportunities were good to share and discuss with the teachers, and later, teachers could share this with the students. SMP Negeri 174 Jakarta is a community service school partner. A seminar about this UAV, its technology, science, and opportunities was held in this school to disseminate knowledge on how the UAV has become important to pay attention to in the near future.